Examples
(0,0) , (1,1)
Step 1
The general equation of a parabola with vertex (h,k) is y=a(x−h)2+k. In this case we have (0,0) as the vertex (h,k) and (1,1) is a point (x,y) on the parabola. To find a, substitute the two points in y=a(x−h)2+k.
1=a(1−(0))2+0
Step 2
Step 2.1
Rewrite the equation as a(1−(0))2+0=1.
a(1−(0))2+0=1
Step 2.2
Simplify a(1−(0))2+0.
Step 2.2.1
Add a(1−(0))2 and 0.
a(1−(0))2=1
Step 2.2.2
Subtract 0 from 1.
a⋅12=1
Step 2.2.3
One to any power is one.
a⋅1=1
Step 2.2.4
Multiply a by 1.
a=1
a=1
a=1
Step 3
Using y=a(x−h)2+k, the general equation of the parabola with the vertex (0,0) and a=1 is y=(1)(x−(0))2+0.
y=(1)(x−(0))2+0
Step 4
Step 4.1
Remove parentheses.
y=(1)(x−(0))2+0
Step 4.2
Multiply 1 by (x−(0))2.
y=1(x−(0))2+0
Step 4.3
Remove parentheses.
y=(1)(x−(0))2+0
Step 4.4
Simplify (1)(x−(0))2+0.
Step 4.4.1
Add (1)(x−(0))2 and 0.
y=(1)(x−(0))2
Step 4.4.2
Multiply (x−(0))2 by 1.
y=(x−(0))2
Step 4.4.3
Subtract 0 from x.
y=x2
y=x2
y=x2
Step 5
The standard form and vertex form are as follows.
Standard Form: y=x2
Vertex Form: y=(1)(x−(0))2+0
Step 6
Simplify the standard form.
Standard Form: y=x2
Vertex Form: y=x2
Step 7